Pengaruh Teladan Pimpinan, Pengawasan, Dan Komunikasi Dua Arah Terhadap Disiplin Kerja Pada Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Muara Enim - Marko Ilpiyanto ilpiyanto; Nidyawati Nidyawati; Deck Sepnonsal (UNIVED Press, 2023)
The purpose of this study was to determine and analyze the influence of leadership role models (X1) partially on work discipline (Y), to determine and analyze the effect of supervision (X2), partially on work discipline (Y), and to determine and analyze the effect of two-way communication. direction (X3) partially towards work discipline (Y) at the Office of Investment and One Stop Services, Muara Enim Regency.In this study using primary data and secondary data, primary data was obtained by distributing questionnaires to 59 employees as respondents who became the sample. The data collection technique used was by conducting observations, interviews and distributing questionnaires at the Office of Investment and One Stop Services, Muara Enim Regency. The data analysis technique used is Multiple Regression Analysis using SPSS 22 Software, in answering the formulation of the research hypothesis testing problem. From the results of data analysis on the variables studied, namely the exemplary leadership variable (X1), supervision (X2), and two-way communication (X3) have a partially significant influence on work discipline (Y).